Variable Nitrogen Fixation in Wild Populus. - Sharon L Doty; Andrew W Sher; Neil D Fleck; Mahsa Khorasani; Roger E Bumgarner; Zareen Khan; Andrew W K Ko; Soo-Hyung Kim; Thomas H DeLuca (PLoS ONE, 2016)
The microbiome of plants is diverse, and like that of animals, is important for overall health and nutrient acquisition. In legumes and actinorhizal plants, a portion of essential nitrogen (N) is obtained through symbiosis with nodule-inhabiting, N2-fixing microorganisms. However, a variety of non-nodulating plant species can also thrive in natural, low-N settings. Some of these species may rely on endophytes, microorganisms that live within plants, to fix N2 gas into usable forms. Here we report the first direct evidence of N2 fixation in the early successional wild tree, Populus trichocarpa, a non-leguminous tree, from its native riparian habitat. In order to measure N2 fixation, surface-sterilized cuttings of wild poplar were assayed using both 15N2 incorporation and the commonly used acetylene reduction assay. The 15N label was incorporated at high levels in a subset of cuttings, suggesting a high level of N-fixation. Similarly, acetylene was reduced to ethylene in some samples. The microbiota of the cuttings was highly variable, both in numbers of cultured bacteria and in genetic diversity. Our results indicated that associative N2-fixation occurred within wild poplar and that a non-uniformity in the distribution of endophytic bacteria may explain the variability in N-fixation activity. These results point to the need for molecular studies to decipher the required microbial consortia and conditions for effective endophytic N2-fixation in trees.